Structural complexity characterizes fine‐scale forest conditions used by Pacific martens. Issue 4 (13th March 2023) - Delheimer, Matthew S.; Moriarty, Katie M.; Munro, Holly L.; Early, Desiree A.; Hamm, Keith A.; Green, Rebecca E.
Abstract: When wildlife species exhibit unexpected associations with vegetation, replication of studies in different locales can illuminate whether patterns of use are consistent or divergent. Our objective was to describe fine‐scale forest conditions used by Pacific martens ( Martes caurina ) at 2 study sites in northern California that differed in forest composition and past timber harvest. We identified denning and resting locations of radio‐marked martens and sampled structure‐ and plot‐level vegetation using standardized forest inventory methods between 2009–2021. Woody structures used by martens were significantly larger than randomly available structures across types (e.g., live tree, snag, log) and at both study sites. Den and rest structures occurred in areas characterized by higher numbers of logs and snags, lower numbers of live trees and stumps, larger diameter live trees and logs, and greater variation in live tree and log diameter. Features of denning and resting locations were largely consistent across study sites and were generally representative of fine‐scale forest heterogeneity and increased structural complexity, conditions that martens have been widely associated with at broader spatial scales (i.e., home range or landscape). The spatial occurrence of denning and resting locations may indicate that fine‐scale structural complexity facilitates marten foraging while reducing predation risk. Our work offers timely and directed information that can guide forest management in the context of increased landscape change. Abstract : We characterized forest conditions used at fine spatial scales by Pacific martens at 2 study sites in northern California over a 12‐year time period (2009−2021). Woody structures (e.g., live and dead trees) used by martens were significantly larger diameter than randomly available structures and consistently occurred in heterogeneous and physically complex forest stands across study sites, despite the sites differing in past land use practices (e.g., timber harvest intensity) and forest composition. Focused retention of such conditions during management activities could benefit martens and a suite of other forest‐dependent wildlife species.